Efektivitas Model Pembelajaran Mind Mapping Terhadap Hasil Belajar IPA di Sekolah Dasar - Raya Rita; Emy Hariati; Leni Malinda (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2021)
This study evaluates the effectiveness of the Mind Mapping learning model compared to conventional methods in improving science learning outcomes in Grade 5 at SDN 060955 Paya Pasir. This research employs a quantitative approach with a quasi-experimental design. The sample consists of two classes, with 33 students in the experimental class and 29 students in the control class. Data analysis uses t-test and N-Gain calculations. The results show that learning using Mind Mapping is significantly more effective in enhancing students' understanding and retention compared to conventional methods, with a t-value (6.121) greater than the t-table value (1.67) at a 5% significance level. This indicates that Mind Mapping can be considered an effective method for teaching science in elementary schools. The implication of this study is the importance of integrating innovative learning models such as Mind Mapping into the school curriculum to enhance learning effectiveness.